DESAIN TUGAS BELAJAR BERBASIS PAMERAN DALAM PEMBELAJARAN DIMENSI TIGA JENJANG PENDIDIKAN MENENGAH - Rahelia Siahaan; Mohamad Rif’at; Sugiatno Sugiatno (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis research intends to develop an exhibition-based learning task design in three-dimensional learning. The learning process uses a scientific approach to improve students' mathematical representation abilities. This reseach uses R&D methods with ADDIE models. The subjects of the research were students in SMA Negeri 1 Sekayam and SMA Negeri 2 Sekayam. The data collection instruments consisted of a validation questionnaire of the exhibition-based learning task design, observation sheets of student learning activities, and test of mathematical representation ability. The results showed that, (1) the exhibition-based learning task design in three-dimensional learning is valid and feasible to use. (2) The learning process occur effectively, based on results of the observation sheet analysis of student learning activities, which shows 7 out of 9 aspects of the activity has been "Good". (3) Students' mathematical representation abilities generally become "Good" after participating in the learning process. Based on the analysis of student learning outcomes that show the average value is 74.69 and 76.67% of students were able to exceed the KKM score limit. The conclusion of this research is the final product of the exhibition-based learning task design in three-dimensional learning developed is valid and feasible to use in three-dimensional learning in the school.Keywords: Exhibition-Based Learning Task Design, Three Dimensional Learning, Learning activity, and Mathematical Representation Abilit